Prolactin Is a Strong Candidate for the Regulation of Luteal Steroidogenesis in Vizcachas (Lagostomus maximus) - S. Proietto; S. A. Cortasa; M. C. Corso; P. I. F. Inserra; S. E. Charif; A. R. Schmidt; N. P. Di Giorgio; V. Lux-Lantos; A. D. Vitullo; V. B. Dorfman; J. Halperin (International Journal of Endocrinology)
Prolactin (PRL) is essential for the maintenance of the corpora lutea and the production of progesterone (P4) during gestation of mice and rats, which makes it a key factor for their successful reproduction. Unlike these rodents and the vast majority of mammals, female vizcachas (Lagostomus maximus) have a peculiar reproductive biology characterized by an ovulatory event during pregnancy that generates secondary corpora lutea with a consequent increment of the circulating P4. We found that, although the expression of pituitary PRL increased steadily during pregnancy, its ovarian receptor (PRLR) reached its maximum in midpregnancy and drastically decreased at term pregnancy. The luteinizing hormone receptor (LHR) exhibited a similar profile than PRLR. Maximum P4 and LH blood levels were recorded at midpregnancy as well. Remarkably, the P4-sinthesizing enzyme 3β-HSD accompanied the expression pattern of PRLR/LHR throughout gestation. Instead, the luteolytic enzyme 20α-HSD showed low expression at early and midpregnancy, but reached its maximum at the end of gestation, when PRLR/LHR/3ß-HSD expressions and circulating P4 were minimal. In conclusion, both the PRLR and LHR expressions in the ovary would define the success of gestation in vizcachas by modulating the levels of 20α-HSD and 3ß-HSD, which ultimately determine the level of serum P4 throughout gestation.